Isolation and Characterization of Adipose-Derived Mesenchymal Stem Cells (ADSCs) from Sheep and Goats - Kanmaz, Yesim Aslan; Yilmaz, Sadik; Ozen, Asuman; Sahin, Fatih Serdar (Univ Agriculture, Fac Veterinary Science, 2024)
Recent therapeutic approaches in animal diseases involve stem cell-based therapies which are showing promising results, particularly with the use of mesenchymal stem cells (MSCs). Our study aimed at isolating and characterizing adipose tissue-derived stem cells (ADSCs) in goats and sheep, evaluating their characteristics mesenchymal nature, and adipogenic, chondrogenic, and osteogenic differentiation potentials. For this purpose, subcutaneous adipose tissues were collected from the inguinal region under sterile conditions from five healthy adult sheep and five goats each slaughtered at a slaughterhouse. MSCs were isolated, cultured, and differentiated into adipogenic, chondrogenic, and osteogenic lineages, followed by respective histochemical staining to confirm differentiation. In passage 3 (P3), the surface markers CD44, CD90, CD105, and CD45 were analyzed using flow cytometry to characterize mesenchymal properties. The cells expressed CD44, CD90, and CD105 but did not express hematopoietic marker CD45, confirming their mesenchymal nature. This study successfully identified ADSCs from sheep and goats as mesenchymal stem cells and characterized their strong trilineage differentiation potential, highlighting their strong therapeutic capabilities and revealing interspecies differences in MSCs properties. These findings provide valuable insights for future MSCs-based therapeutic applications in veterinary regenerative medicine, particularly for economically and clinically important species.
Keywords: Adipose-derived mesenchymal stem cell; Sheep; Cell differentiation; Flow cytometry; Goat